2022
DOI: 10.3389/fimmu.2022.840620
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells in Patients With Acute Pancreatitis With Increased Inhibitory Function

Abstract: Acute pancreatitis (AP) is pancreatic or systemic inflammation without or with motion organ dysfunction. Severe acute pancreatitis (SAP) is the main cause of death for patients with AP. A pro-/anti-inflammatory imbalance is considered the key regulation of disease severity. However, the real mechanism of SAP remains unclear. This study aimed to identify the frequency and specific roll of myeloid-derived suppressor cell (MDSC) in AP. We evaluated MDSC frequency and disease severity by analyzing MDSCs in the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A large number of studies have shown that a variety of immune cells are involved during the onset of AP, and the imbalance between pro-in ammatory and anti-in ammatory immune systems is an important mechanism that promotes disease progression [8][9][10][11] .However, the relationship at the genetic level is still unclear, so we used MR analysis and based on a large amount of public genetic data found that AP has signi cant causal effects on four types of immune cells, CD14 + CD16-, CD28, CD14+, and Mo MDSC AC. (P < 0.05), these results indicate that immune cells may be an important factor in uencing AP, and also mean that immune cells at the genetic level play an important role in the pathogenesis of AP.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that a variety of immune cells are involved during the onset of AP, and the imbalance between pro-in ammatory and anti-in ammatory immune systems is an important mechanism that promotes disease progression [8][9][10][11] .However, the relationship at the genetic level is still unclear, so we used MR analysis and based on a large amount of public genetic data found that AP has signi cant causal effects on four types of immune cells, CD14 + CD16-, CD28, CD14+, and Mo MDSC AC. (P < 0.05), these results indicate that immune cells may be an important factor in uencing AP, and also mean that immune cells at the genetic level play an important role in the pathogenesis of AP.…”
Section: Discussionmentioning
confidence: 99%
“…A proportion of circulating HLA-DR −/low monocytes seen in both AP and COVID-19 patients have been identified as CD14 + CD11b + HLA-DR −/low CD15 − monocytic myeloid-derived suppressor cells (M-MDSCs); these cell types may cloud earlier studies on the topic, as they could be misidentified as HLA-DR −/low classical monocytes [ 174 , 175 , 176 ]. M-MDSCs are characterized by their potent immunosuppressive effects on other immune cells, especially T cells, through various mechanisms including secretion of arginase-1 (Arg-1), and inducible nitric oxide synthase, production of reactive oxygen and nitrogen species, secretion of cytokines including TGF-β and IL-10, and induction of regulatory T cells [ 175 ].…”
Section: The Role Of Mhla-dr In Ap and Covid-19mentioning
confidence: 99%
“…The proportion of M-MDSCs in peripheral blood mononuclear cells correlates with AP severity as reflected by plasma CRP levels, APACHE II score, and length of stay [ 174 ]. Increased levels of Arg-1 and ROS can further be observed in AP patients, especially those with a severe clinical course [ 174 ].…”
Section: The Role Of Mhla-dr In Ap and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…When activated and accumulating in peripheral lymphoid tissues and the tumors, they are implicated in suppressing immunity and promoting tumor progression. The different function and differentiation of MDSCs are related to the different phenotype of the TME ( 18 ).…”
Section: Role Of the Tme In Immunotherapymentioning
confidence: 99%